European Integration in View of Euroscepticism - Pleśniarska, Aleksandra (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
Eurosceptical views are more and more often evident in the programmes and activities of European political parties, and are manifested in the political debate transpiring in Member States. Is Euroscepticism an opportunity or a threat for the future of the idea of European integration? Does it threaten the cohesion of the European project? The main aim of this article is to answer these questions.Euroscepticism and the categorizations it breaks down into are defined in the article. Empirical analysis and a review of the literature are used to illustrate the importance of Eurosceptics in the European Parliament. This study identifies why Eurosceptical views in Europe have become more popular, pointing to the existence of many European crises, including in the economy, migration and democracy.The number of Eurosceptics in the EP has increased, but they come from different political groups. If their opinions are to be seen as an opportunity for the future of the EU, their demands must be consolidated and infused with greater coherence. Eurosceptical views should not be marginalized in the context of the further development of the EU.